The Role of Law Enforcement Agencies in the Effort of Corruption Prevention and Eradication in the Perspective of Progressive Law in Indonesia - Kusumawati, Intan; Supriyono; Suny Atmadja, Iin; Hasanah, Enung; Cahyati, Suci (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is a white-collar crime that is difficult to eradicate. To eradicate corruption, the optimization of the act of corruption prosecution through an integrated paradigm with qualified professional law enforcement officers is necessary. This article seeks to explore the role of the law's supremacy in Indonesia in the prevention and eradication of corruption from a progressive law perspective through a literature review. The results of the study show that internal and external factors cause obstacles in coping with corruption cases in Indonesia. Law enforcement efforts against corruption will succeed if law enforcement officers play an active role in the efforts of prevention and dealing with corruption cases objectively. Law supremacy can be upheld if the character of its human resources has high integrity, discipline, principles abiding, and consistency with implementing a new model of criminal law enforcement based on the principles of progressive law.